Comparative Analysis of Transposable Elements in the Genomes of Citrus and Citrus-Related Genera - Yilei Wu; Fusheng Wang; Keliang Lyu; Renyi Liu (Plants, 2024)
Transposable elements (TEs) significantly contribute to the evolution and diversity of plant genomes. In this study, we explored the roles of TEs in the genomes of Citrus and Citrus-related genera by constructing a pan-genome TE library from 20 published genomes of Citrus and Citrus-related accessions. Our results revealed an increase in TE content and the number of TE types compared to the original annotations, as well as a decrease in the content of unclassified TEs. The average length of TEs per assembly was approximately 194.23 Mb, representing 41.76% (Murraya paniculata) to 64.76% (Citrus gilletiana) of the genomes, with a mean value of 56.95%. A significant positive correlation was found between genome size and both the number of TE types and TE content. Consistent with the difference in mean whole-genome size (39.83 Mb) between Citrus and Citrus-related genera, Citrus genomes contained an average of 34.36 Mb more TE sequences than Citrus-related genomes. Analysis of the estimated insertion time and half-life of long terminal repeat retrotransposons (LTR-RTs) suggested that TE removal was not the primary factor contributing to the differences among genomes. These findings collectively indicate that TEs are the primary determinants of genome size and play a major role in shaping genome structures. Principal coordinate analysis (PCoA) of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) identifiers revealed that the fragmented TEs were predominantly derived from ancestral genomes, while intact TEs were crucial in the recent evolutionary diversification of Citrus. Moreover, the presence or absence of intact TEs near the AdhE superfamily was closely associated with the bitterness trait in the Citrus species. Overall, this study enhances TE annotation in Citrus and Citrus-related genomes and provides valuable data for future genetic breeding and agronomic trait research in Citrus.